Pengaruh Pengembangan Karir, Beban Kerja Dan Insentif Terhadap Loyalitas Pegawai - Eka Suryaningsih; Syaiful Anwar (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
This study aims to determine the effect of career development, workload and incentives on employee loyalty. Data was collected using a questionnaire on employees of the Public and State Property Section, Directorate General of Islamic Community Guidance, Ministry of Religion of the Republic of Indonesia in Jakarta. The sampling technique is saturated with a total of 35 respondents. The analytical tool used is descriptive (primary data) by using a questionnaire assisted by a Likert scale and given to respondents. The analytical tool used is SPSS software version 25. The results of multiple linear analysis using multiple linear regression analysis method. Y = 2.382 + 0.202 (X1) + 0.452 (X2) + 0.151 (X3) + €, so that it can be partially concluded that Career Development does not have a significant effect on Employee Loyalty, Workload and Incentives have a significant effect on Employee Loyalty in General and Property Sections State, Directorate General of Islamic Community Guidance, Ministry of Religion of the Republic of Indonesia in Jakarta.